The Role of GLP-1 Signaling in Hypoglycemia due to Hyperinsulinism - Danowitz, Melinda; De Leon, Diva D. (Frontiers in Endocrinology, 2022)
Incretin hormones play an important role in the regulation of glucose homeostasis through their actions on the beta cells and other tissues. Glucagon-like peptide-1 (GLP-1) and glucose dependent insulinotropic polypeptide (GIP) are the two main incretins and are secreted by enteroendocrine L- and K-cells, respectively. New evidence suggests that incretin hormones, particularly GLP-1, play a role in the pathophysiology of hyperinsulinemic hypoglycemia. In individuals with acquired hyperinsulinemic hypoglycemia after gastrointestinal surgery, including Nissen fundoplication and gastric bypass surgery, the incretin response to a meal is markedly increased and antagonism of the GLP-1 receptor prevents the hyperinsulinemic response. In individuals with congenital hyperinsulinism due to inactivating mutations in the genes encoding the beta cell KATP channels, the GLP-1 receptor antagonist, exendin-(9-39), increases fasting hypoglycemia and prevents protein-induced hypoglycemia. Studies in human and mouse islets lacking functional KATP channels have demonstrated that the effect on plasma glucose is at least in part mediated by inhibition of insulin secretion resulting from lower cytoplasmic cAMP levels. The understanding of the role of incretin hormones in the pathophysiology of hyperinsulinemic hypoglycemia is important for the exploration of the GLP-1 receptor as a therapeutic target for these conditions. In this article, we will review incretin physiology and evidence supporting a role of the incretin hormones in the pathophysiology of hyperinsulinemic hypoglycemia, as well as results from proof-of concept studies exploring a therapeutic approach targeting the GLP-1 receptor to treat hyperinsulinemic hypoglycemia.